(untitled) (Academicia Globe: Inderscience Research, 2022)
The article deals with the issues of labor legislation of the Republic of Uzbekistan in the period of its independence. The current legislation is analyzed, taking into account the improvement of its norms in the current stage ofthe country’s development.